Complete Traumatic Luxation of the Eyeball - Manpreet Singh (Knowledge E, 2021)
Abstract Purpose: To report the computed tomography features of a case with complete luxation of the globe after a road traffic accident. Case Report: A 35-year-old male presented with pain, loss of vision, and bleeding from the left eye 48 hr after a road traffic accident. The ophthalmic examination of the left upper and lower eyelids showed edema with subcutaneous hematoma, crepitus, and complete blepharoptosis. On retracting the eyelids, the left eyeball was not visible and the patient was not able to perceive light. The left temporal region appeared filled with a soft, palpable globular structure situated beneath the temporalis muscle. A non-contrast computed tomography (NCCT) of the head and orbits showed a comminuted and displaced fracture of the floor, medial, and lateral orbital walls in addition to a displaced tripod fracture of the left zygomatic bone. The intact left eyeball was seen below the temporalis muscle without any optic nerve or extraocular muscle attachment. The virtual reality reconstruction highlighted a contributory supero-temporal defect in the bony orbit, which appeared large enough to accommodate the intact eyeball. Conclusion: The computed tomography of the orbits provided a detailed location of the luxated eyeball and provided guidance in further management of the case.